Success of community-based directly observed anti-tuberculosis treatment in Mongolia - Dobler, C.; Korver, S.; Batbayar, O.; Oyungtsetseg, S.; Tsolmon, B.; Wright, Cameron; Solongo, B.; Marais, B. (Churchill Livingstone, Journal production department, 2015)
BACKGROUND: Many countries restrict access to directly observed therapy (DOT) for tuberculosis (TB) to government health facilities. More innovative approaches are required to reduce non-adherence, improve patient outcomes and limit the risk of selecting drug-resistant strains. METHODS: We performed a retrospective cohort study in sputum smear-positive patients treated with community-based DOT (home-based DOT or 'lunch' DOT, whereby DOT is provided with a free daily meal once sputum smear conversion has been documented), and conventional clinic-based DOT in Ulaanbaatar, the capital of Mongolia, in 2010-2011. We compared treatment success using community-based home DOT vs. conventional clinic DOT and describe treatment completion rates using lunch DOT. RESULTS: The overall treatment success among new sputum smear-positive TB patients was 85.1% (1505/1768). Patients receiving community DOT had higher cure rates (294/327, 89.9% vs. 1112/1441, 77.2%; aOR 2.66, 95%CI 1.81-3.90) and higher treatment success (306/327, 93.6% vs. 1199/1441, 83.2%; aOR 2.95, 95%CI 1.85-4.71, P < 0.001) than those treated with clinic DOT. Apart from one death, treatment completion was 100% among patients who received lunch DOT after sputum smear conversion. CONCLUSIONS: Community DOT improved treatment success in Ulaanbaatar, Mongolia. It should now be scaled up to be made available for more patients and in all regions of the country.